Աշուղ Ղունկիանոսի ստեղծագործությունները ուշ միջնադարյան հայ բանաստեղծության համատեքստում - Ա. Ս. Հարությունյան (ՀՀ ԳԱԱ հրատ.)
В многовековом армянском культурном наследии ашугская поэзия занимает особое место. Она пережила бурное развитие особенно в XVIII в. In the Armenian rich cultural heritage the folk (ashugh's) poetry occupies a special place. It flourishes especially in the 18th century.
Keywords: Literature; Language and Literature